2019
DOI: 10.1186/s12902-019-0354-7
|View full text |Cite
|
Sign up to set email alerts
|

Poor short-term glycemic control in patients with type 2 diabetes impairs the intestinal mucosal barrier: a prospective, single-center, observational study

Abstract: Background To determine the relation between daily glycemic fluturation and the intestinal mucosal barrier dysfunction in type 2 diabetes mellitus (T2DM). Methods Totally 66 patients with T2DM were enrolled, 33 healthy volunteers were also recruited according to the enrolled patients’ gender and age in a ratio of 2: 1. Patients were bisected by the median of endotoxins level into low(< 12.31 μ/l, n = 33) and high(≥12.31 μ/l, n = 33) blood endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
(31 reference statements)
2
21
0
Order By: Relevance
“…Compared with sustained hyperglycemia, glycemic variability has more deleterious effects in the pathogenesis of diabetic complications ( Beck et al, 2019 ; Nusca et al, 2018 ). An observational study has found that type 2 diabetic patients incapable of maintaining stable PG levels were more likely to have IB injury ( Shen et al, 2019 ), in other words, glycemic variability might be associated with IB dysfunction. In this study, ΔPG was used to indicate the glycemic variability, and the results showed that the serum I-FABP level was positively correlated with ΔPG in the inpatient group.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with sustained hyperglycemia, glycemic variability has more deleterious effects in the pathogenesis of diabetic complications ( Beck et al, 2019 ; Nusca et al, 2018 ). An observational study has found that type 2 diabetic patients incapable of maintaining stable PG levels were more likely to have IB injury ( Shen et al, 2019 ), in other words, glycemic variability might be associated with IB dysfunction. In this study, ΔPG was used to indicate the glycemic variability, and the results showed that the serum I-FABP level was positively correlated with ΔPG in the inpatient group.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental diabetes mellitus and high glucose exposure have been shown to cause an impairment of barrier function. [23][24][25][26][27][28][29] A recent study reported a decrease in TEER in human corneal epithelial cells exposed to 30 mM glucose. 30 Our data are in agreement with this report 30 and additionally demonstrate that corneal epithelial barrier function can also be compromised by moderately high glucose (15 mM).…”
Section: Discussionmentioning
confidence: 99%
“…The plasma from each participants was collected for intestinal mucosal barrier function analysis. The parameters of gut mucosal barrier function such as endotoxin (LPS), D-lactate, and diamine oxidase (DAO) were detected by a dry chemical method using the Intestinal Mucosal Barrier Biochemical Index Analysis System (JY-DLT, Beijing Zhongsheng Jinyu Diagnostic Technology Co., Ltd., China) [19,21,22]. The experiments were undergone according to the protocols suggested by the manufacturer and conducted within 4 h after plasma extraction.…”
Section: Intestinal Mucosal Barrier Function Analysismentioning
confidence: 99%